Resistive switching in microscale anodic titanium dioxide-based memristors. (January 2018) - Aglieri, V.; Zaffora, A.; Lullo, G.; Santamaria, M.; Di Franco, F.; Lo Cicero, U.; Mosca, M.; Macaluso, R.
Abstract: The potentiality of anodic TiO2 as an oxide material for the realization of resistive switching memory cells has been explored in this paper. Cu/anodic-TiO2 /Ti memristors of different sizes, ranging from 1 × 1 μm 2 to 10 × 10 μm 2 have been fabricated and characterized. The oxide films were grown by anodizing Ti films, using three different process conditions. Measured IV curves have shown similar asymmetric bipolar hysteresis behaviors in all the tested devices, with a gradual switching from the high resistance state to the low resistance state and vice versa, and a ROFF /RON ratio of 80 for the thickest oxide film devices.